Implementation of Qur'an Hadith Learning at MTs Al-Umm Karawang - Naila Waridatus Sa’adah; Firda Amalia; Hidayatul Mustafidah; Maulida Hasanah; Naufal Rafif Agustian; Debibik Nabilatul Fauziah (Qoumun: Jurnal Pengabdian Masyarakat, 2025)
The teaching of Al-Qur'an Hadith plays a vital role in shaping students' spiritual and moral values at the madrasah level. This study aims to analyze the implementation of Al-Qur'an Hadith learning at MTs Al Umm Karawang, focusing on the stages of planning, implementation, and evaluation. A descriptive qualitative method was used, with data collected through observation, interviews, and documentation. The findings reveal that lesson planning is carried out by preparing instructional materials aligned with the current curriculum. The learning process involves various methods, such as lectures, question-and-answer sessions, discussions, and memorization of selected verses. Evaluation is conducted through oral, written, and practical memorization tests. Overall, the implementation of learning is quite effective, although challenges such as limited time and inadequate supporting facilities remain.Therefore, it is crucial to improve teaching strategies and provide better facilities to enhance the effectiveness of the learning process.